Design and application of an arm support capable of observing puncture sites - MI, Peipei; LI, Yanfen; XU, Yuanle; ZHOU, Enhui (Chinese Journal of Integrative Nursing, 2023)
Surgical nurses should pay attention on safte body position of patients during surgery. This paper introduced the design and application of an arm support capable of observing puncture sites. It has advantages of esay-to-use, faciliating puncture sites observation and keeping warm, could be effective to improive the patient comfort and surgical safety) (手术体位安全是手术室护理人员关注的重点。本研究介绍一款开窗式手臂托架的设计和使用方法, 具有使用方便、操作灵活、便于观察、保暖等优点, 能有效提高患者舒适度和安全性。)